The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10152-015-0441-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biology of the crab Goniopsis cruentata: geographic variation of body size, sexual maturity, and allometric growth

Abstract: Geographic variation of phenotypic traits is common across species and is often associated with variation in environmental conditions. Here, we found larger bodies and larger size at maturity in a northward, lower latitude population of the crab Goniopsis cruentata, which inhabits a hotter, drier environment in comparison with a southward, higher latitude population. Furthermore, the juvenile male gonopods grow more relative to body size in the population characterized by maturation at a smaller size. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…A.3). The nitrogen demand of this species is due to its faster growth rate than that of U. cordatus (e.g., Pinheiro et al, 2005;Reis et al, 2015, Leite et al, 2014, De Lira et al, 2015. In animals, an investment in growth increases the nitrogen demand during foraging (Sterner and Elser, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A.3). The nitrogen demand of this species is due to its faster growth rate than that of U. cordatus (e.g., Pinheiro et al, 2005;Reis et al, 2015, Leite et al, 2014, De Lira et al, 2015. In animals, an investment in growth increases the nitrogen demand during foraging (Sterner and Elser, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, diverging from the results found in this study, Reis et al (2015) presented results for Goniopsis cruentata in which juvenile specimens showed negative allometry and adults positive allometry for the weight/growth relationship. Individual allometries for different locations observed in these crabs indicate that geographic variation (factors such as temperature) may influence the body size determination of Brachyura such as G. cruentata because, according to Lira et al (2015), local conditions influence variations in their biological characteristics. Therefore, geographic variations may be associated with differences in body size, maturity and variation in reproductive characteristics, a behaviour that is present and well defined in other organisms (Olalla-Tárraga et al 2009).…”
Section: Linear Morphometrymentioning
confidence: 99%
“…structure (Botelho et al 2004), sexual maturity (Moura and Coelho 2004), reproduction and growth, morphological and physiological sexual maturation, reproductive period, fecundity and the influence of environmental factors on reproduction Fransozo 2003, 2005), reproductive aspects (Lira and Calado 2013), reproductive biology (Garcia and Silva 2006), growth (traditional morphometry) (Lira et al 2015) and mangrove environmental quality (Ferreira et al 2019). However, there is still a lack of studies exploring and describing the shape of G. cruentata and information stemming from it using the geometric morphometry technique.…”
mentioning
confidence: 99%